ANALISIS FRAMING PEMBERITAAN SILUET PINOKIO JOKOWI PADA MEDIA ONLINE DETIK.COM DAN SUARA.COM - Noval Setiawan (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2021)
This study aims to explain how online media framing sees an event being reported. And how is the influence of media ownership on online media behavior to keep a neutral and objective position on their news. The object of research is the coverage of